Air-cooled window for a recuperated solar-dish Brayton cycle using a turbocharger and short-term thermal storage - Le Roux, Willem G. (University of Pretoria, 2022)
Dissertation (MEng (Mechanical Engineering))--University of Pretoria, 2022.